A Comprehensive Study of Manganese Deposition and Side Reactions in Li-Ion Battery Electrodes. Issue 12 (16th September 2017) - Lee, Yoon Koo; Park, Jonghyun; Lu, Wei
Abstract : A thorough investigation of both manganese (Mn) deposition onto graphite and its side reactions was conducted based on complementary techniques including CV, EIS, GCPL, ICP-OES, SEM and EDS. Each measurement revealed a specific aspect of the degradation phenomena, which taken together all pointed in a common direction. This study focused on 1) deposition mechanisms and effects of manganese ions on the SEI layer; 2) the effects of manganese deposition on electrochemical performance; and 3) direct observation of decomposed layers induced by manganese deposition. It was confirmed that adding Mn(PF6 )2 salt in the electrolyte results in severe capacity decrease and impedance rise. It is found that manganese ions in the electrolyte participate to generate Mn-containing SEI layers when depositing onto the graphite surface accompanied by additional side reactions. Interestingly, before manganese ions deposit onto the graphite electrode, they enhance cell capacity due to additional oxidation reactions. It is found that the reaction of manganese ions changes with the voltage conditions during charge or discharge and the lithiation status of the graphite electrode.